Kajian Penggunaan Pupuk Organik Dan Dampaknya Terhadap Pertanian Berkelanjutan - Zendrato, Martirah Warni; Gulo, Nice Anjelin; Nazara, Linda Heppy Karisda; Waruwu, Victoris Julman; Gulo, Selianus; Gulo, Romanus Restu; Zebua, Helmin Parida (Jurnal Ilmu Pertanian dan Perikanan, 2024)
This research aims to examine the use of organic fertilizer and its impact on environmentally friendly sustainable agriculture. This research was carried out through literature studies from various related literature. Organic fertilizer which comes from natural materials such as plant residues and livestock waste, has benefits in improving the structure of the soil, increasing water retention capacity, and supporting ecosystem sustainability. This research discusses the types of organic fertilizer. From the results of the study, it was found that organic fertilizer was able to increase soil fertility, support microbial activity, and reduce dependence on the use of chemical fertilizers. However, challenges such as the lower nutrient content compared to chemical fertilizers, the decomposition time which takes quite a long time, and even the lack of understanding of farmers are the main obstacles. In conclusion, this study emphasizes that organic fertilizer is an important element in sustainable agriculture, especially in maintaining soil quality and the environment.